If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(2X + 15) + -9X = 69 Reorder the terms: 5(15 + 2X) + -9X = 69 (15 * 5 + 2X * 5) + -9X = 69 (75 + 10X) + -9X = 69 Combine like terms: 10X + -9X = 1X 75 + 1X = 69 Solving 75 + 1X = 69 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-75' to each side of the equation. 75 + -75 + 1X = 69 + -75 Combine like terms: 75 + -75 = 0 0 + 1X = 69 + -75 1X = 69 + -75 Combine like terms: 69 + -75 = -6 1X = -6 Divide each side by '1'. X = -6 Simplifying X = -6
| 3n+2=4 | | x2/3-8x1/3+15=0 | | 6x-15=4x+7 | | (13-z)+2=5 | | (1/10)+(4/9)/(1/5)+(5/9) | | 2x-x^2=-15 | | 14+7x=2x-11 | | (-3x)-(-13)=5 | | y+14y+13=0 | | 14x-13=3+2x+8 | | 1/8a=7 | | 2*2(4*4)+6*6-6= | | x/3+x/5=8/5 | | 3=2x+-3 | | (13-z)+2=18 | | 48p+30q= | | 2x^5=72x^3 | | 11y/14 | | y-.8=4.75 | | (9x-8)-(x+4)= | | -a/9=11/30 | | 6z=18+3z | | 7875/175 | | 4x+4=-x^2 | | 4(x-2)-2(x+11)=4 | | 3y/5-y/5 | | 5f+10=9+5f | | -6(4-1)=12r | | x(2x-3)+x(3x-2)=(5x+6)(x-1) | | (y/14)/(11/14) | | (Z-2)+5=10 | | 6t-9=4t-3 |